An experience of gynaecological laparoscopic surgeries at low resource setting. - Agrawal, Ajay; Chandra Regmi, Mohan Chandra Regmi; Rijal, Pappu; Thakur, Achala; Basnet, Pritha (Birat Journal of Health Sciences, 2020)
Introduction: Evolution of laparoscopy has revolutionised the field of gynaecological surgery for more than 40 years.Owing to the long learning curve, added expenses and lack of awareness among patients and surgeons, its introduction and development in Nepal is not upto the timeline. Gynaecologic laparoscopy (GL) seems to be introduced at BP Koirala institute of Health Sciences, Dharan,Nepal (BPKIHS) since 2002. It remained in latency because of widespread lack of equipment and skilled personnel. Some laparoscopic procedures like diagnostic laparoscopy, laparoscopic tubal ligation and very few laparoscopic assisted vaginal hysterectomy (LAVH) were done from 2002 - 2012 (10 years). Since then more gynecologists have been trained in GL which has contributed to expansion of GL. Objective: The objective of this study is to study and share trends of gynaecological laparoscopic surgeries performed at BPKIHS. Methodology: All the patients undergoing GL surgeries have been analyzed for the indication, type of procedure, conversion and its complications. We took data from operation theatre register and patient case sheet from July 2004 to May 2018. We divided this period into two phase viz Phase 1: July 2004-June 2013 and Phase 2: July 2013- till May 2018. Results: Total number of GL done in this period was 427. Out of which 102 cases were from phase one and rest of the cases were done in five years of phase II. Number of operative laparoscopy has increased in phase 2 compared to phase 1. In last five years there was155 (47.6%) cases of adnexal surgery, 77 (23.6%) cases of diagnostic laparoscopy.Total laparoscopic hysterectomy was done in 25 (7.6%) cases. Conversion to laparotomy was done in4.6% (n=15) cases. Overall 12(3.7%) patient had major complications. Oral diet started at 4-6th hour post-operatively, and mobilization started after 24 hours. Seventy percent of patient had a hospital stay of 2days and rest stayed for 3 days. Conclusions: There is rising trend in operative GL at BPKIHS. We are facing less complication with expanding experience. There has been good learning from each case. GL has well demonstrated its advantages of reducing postoperative pain and morbidity, short hospital stay, and less postoperative recovery time. We have plans to get new gadgets and expand services in GL.